2020
DOI: 10.3389/fmicb.2020.00862
|View full text |Cite
|
Sign up to set email alerts
|

The Cultivable Bacterial Microbiota Associated to the Medicinal Plant Origanum vulgare L.: From Antibiotic Resistance to Growth-Inhibitory Properties

Abstract: Origanum vulgare L. Associated Microbiota conclusion, this study regarded the characterization of O. vulgare L. chemotype and of the bacterial communities associated to this medicinal plant, also allowing the evaluation of antibiotic resistance and antagonistic interactions. This study provided the bases for further analyses on the possible involvement of endophytic bacteria in the production of antimicrobial molecules that could have an important role in clinical and therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 50 publications
3
41
0
1
Order By: Relevance
“…They were abundant members of the leaf communities of both MPs, but differences on the genus level were monitored, indicating that each plant selects for its specific bacterial community. As our and data from other studies show, bacteria can also be prominent members of the flower communities, in particular Enterobacteriaceae (Shade et al, 2013;Aleklett et al, 2014;Junker and Keller, 2015;Wei and Ashman, 2018;Castronovo et al, 2020). In fact, Enterobacteriaceae appear to be specifically associated to the style and stamen of the flower as reported for the tree M. polymorpha (Junker and Keller, 2015).…”
Section: Microbial Taxa Of the Plant And Soil Communitiessupporting
confidence: 77%
See 2 more Smart Citations
“…They were abundant members of the leaf communities of both MPs, but differences on the genus level were monitored, indicating that each plant selects for its specific bacterial community. As our and data from other studies show, bacteria can also be prominent members of the flower communities, in particular Enterobacteriaceae (Shade et al, 2013;Aleklett et al, 2014;Junker and Keller, 2015;Wei and Ashman, 2018;Castronovo et al, 2020). In fact, Enterobacteriaceae appear to be specifically associated to the style and stamen of the flower as reported for the tree M. polymorpha (Junker and Keller, 2015).…”
Section: Microbial Taxa Of the Plant And Soil Communitiessupporting
confidence: 77%
“…Other comparative studies have shown that the microbiome of different plants is distinct, reflecting the specific feature of the given plant and its environment ( Copeland et al, 2015 ; Lumactud and Fulthorpe, 2018 ; Massoni et al, 2020 ). The various microbial taxa include commensals, potential pathogens but also probiotic and host growth-promoting members interacting with other microbes and the host plant in various mutualistic and antagonistic and still little understood ways ( Hardoim et al, 2015 ; Berg et al, 2016 ; Brader et al, 2017 ; Castronovo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, but not least, endophytes could be selected in relation to their antimicrobial resistance phenotype as a response to antimicrobial molecules produced by microorganisms in the same ecological niche [ 31 ]. This hypothesis has been suggested in the case of the three MPs, E. purpurea and E. angustifolia [ 13 , 31 , 36 ], and O. vulgare [ 37 ]. Here, different plant compartments were characterized by different antimicrobial resistance patterns and antagonistic interactions.…”
Section: Introduction To Medicinal Plantsmentioning
confidence: 95%
“…Human health is seriously threatened by the constant emergence of multi-drug resistant (MDR) microorganisms and the drying up of the pipelines of new antibiotic discovery. Many studies have demonstrated that bacterial endophytes of MPs could be promising sources of antimicrobial molecules [ 37 , 38 , 39 , 68 , 99 , 100 ]. On the other hand, since 1985, very few new classes of antibiotics have been discovered, highlighting the need for an alternative strategy to isolate effective antibiotics from endophytes [ 69 ].…”
Section: Biotechnological and Therapeutical Applicationsmentioning
confidence: 99%